Petrochronology methods and applications - Kohn, Matthew J.; Engi, Martin; Lanari, Pierre (Reviews in mineralogy and geochemistry ;, 2017)
Reviews in Mineralogy & Geochemistry (RiMG) volumes contain concise advances in theoretical and/or applied mineralogy, crystallography, petrology, and geochemistry. With an Impact Factor of 4.760 RiMG is number 1 in the category Mineralogy in the 2014 Thomson Reuters Journal Citation Report/Science Edition.